2014
DOI: 10.1080/08870446.2014.991734
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of belonging: Experimental manipulation of social inclusion to enhance psychological and physiological health parameters

Abstract: ObjectiveAcute changes in social belonging are important triggers for alterations in health and wellbeing, yet research has emphasised the negative effects of 'exclusion' at the expense of evaluating the potentially positive effects of 'inclusion'. This study examined the impact of acute belonging on physiological and psychological outcomes. Design & Main Outcome MeasuresA healthy population (n=138) were randomly allocated to 'included' or 'excluded' task conditions. Condition-dependent differences in pre/duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 46 publications
1
22
0
1
Order By: Relevance
“…This suggests that using exercise to improve physical health, can lead to improvements in mental health. Begen and Turner-Cobb (2015) highlight that research has often focussed on the negative effects of exclusion, rather than the positive impact of inclusion.…”
Section: Impact Of Physical Exercise On Mental Healthmentioning
confidence: 99%
“…This suggests that using exercise to improve physical health, can lead to improvements in mental health. Begen and Turner-Cobb (2015) highlight that research has often focussed on the negative effects of exclusion, rather than the positive impact of inclusion.…”
Section: Impact Of Physical Exercise On Mental Healthmentioning
confidence: 99%
“…The literature reveals that an individual's sense of belonging is an important psychological construct with formative implications for both psychological and physical health across the life span (e.g., Poulton, Caspi, & Milne, 2002;Wadsworth, Thomsen, Saltzman, Connor-Smith, & Compas, 2001). Past research that has investigated belonging has found that those who report a high sense of belonging are more likely to report psychological benefits such as wellbeing, increased self-esteem, and positive mood (Begen & Turner-Cobb, 2015;Newman, Lohman, & Newman, 2007), improved memory (Haslam et al, 2010), positive life transitions (Haslam et al, 2008;Iyer, Jetten, Tsivrikos, Haslam, & Postmes, 2009), and reduced stress . Benefits associated with physical functioning have also been reported and include reduced risk of stroke (Boden-Albala, Litwak, Elkind, Rundek, & Sacco, 2005), lowered disease risk (Cohen & Janicki-Deverts, 2009), and reduced mortality (Holt-Lunstad, Smith, & Layton, 2010;Jetten, Haslam, Haslam, & Branscombe, 2009).…”
mentioning
confidence: 99%
“…At present, relationships appear to be the main avenue, and perhaps the only means, by which self-esteem can truly be affirmed. Our social environment influences health and wellbeing (Begen & Turner-Cobb, 2015). And so are the evolutionary and practical benefits of inclusion in the naturalistic environment (Leary, 2010).…”
Section: Resultsmentioning
confidence: 99%